Respuestas

2013-01-18T02:18:40+01:00

99 = 33x + 3(5 + 3x)

99 = 33x + (5 * 3 + 3x * 3)

99 = 33x + (15 + 9x)

99 = 15 + 33x + 9x

99 = 15 + 42x 

99 + -42x = 15 + 42x + -42x
42x + -42x = 0 99 + -42x 
15 + -99 = -84 -42x = -84
-42'. x = 2
 x = 2

2013-01-18T02:54:47+01:00

99 = 33x + 3(5 + 3x)

99 = 33x + (5 * 3 + 3x * 3)

99 = 33x + (15 + 9x)

99 = 15 + 33x + 9x

99 = 15 + 42x 

99 + -42x = 15 + 42x + -42x
42x + -42x = 0 99 + -42x 
15 + -99 = -84 -42x = -84
-42'. x = 2
 x = no se si estoy bien